KESIAPAN PELAKSANAAN TEACHING FACTORY KOMPETENSI KEAHLIAN TEKNIK KENDARAAN RINGAN SMK NEGERI 3 YOGYAKARTA - Bagas Ary Pradana; Herminarto Sofyan (Journal of Automotive Technology and Education, 2024)
SMK N 3 Yogyakarta is one of the vocational schools appointed by Presidential Decree No. 9 of 2016 concerning Vocational Revitalization. SMK N 3 Yogyakarta is a reference vocational school that must implement a program, teaching factory but the Light Vehicle Engineering Skills Competence has not implemented learning on a base teaching factory. This study aims to determine the level of readiness of light vehicle engineering competence in SMK N 3 Yogyakarta if-based learning is carried out in a teaching factory. This research is a type of descriptive research. Collecting data using questionnaires, observation, and documentation. Respondents of this study were productive teachers of light vehicle engineering skills at SMK N 3 Yogyakarta. The data analysis technique used descriptive statistics. The conclusions from the research results are: (1) the level of teacher readiness if-based learning is carried out is teaching factory in the ready category, (2) the level of readiness for cooperation with industry if-based learning is carried out is teaching factory in the ready category, and (3) the level of infrastructure readiness if implemented-based learning is teaching factory in the very ready category.